Epidemiological Study and Clinical Presentation of Urinary Tract Infection - Suhad Asad Mustafa; Raya Kh. Yashooa; Muhammmed Ahmad Muhamad; Karzan Abdulmuhsin Mohammad (QAASPA Publisher, 2023)
A urinary tract infection (UTI) is an immune response of the urothelium to bacterial invasion, bacteriuria (presence of bacteria in urine) and pyuria (presence of white blood cells in urine) are characteristic indicators of UTI. Prompt and effective management of UTIs is crucial to prevent complications, such as kidney infections and recurrent infections, and to alleviate symptoms, improve quality of life, and minimize antibiotic resistance. The aim of this study was to investigate the incidence, antibiotic resistance, medical treatment, causative agents, diagnosis, and prevention of urinary tract infections (UTIs) in Sulaymaniah city. A total of 60 patients from Sulaymaniah Teaching Hospital were included in the study. The most commonly diagnosed conditions were acute pyelonephritis and cystitis. Various evaluations were conducted, including history taking, physical examination, and diagnostic tests. Mid-stream urine samples were collected for culture and sensitivity analysis. The duration of symptoms such as dysuria, fever, and frequency varied, ranging from 1 to 3 days. During medical examinations, suprapubic tenderness was the most commonly observed finding. Dysuria was reported as the predominant symptom by 19 patients. The majority of patients fell within the age range of 21-40 years. The study findings indicated a higher prevalence of UTIs among females. The most frequently identified causative microorganism was Escherichia coli (E. coli), which accounted for approximately 90% of cases. Gentamycin emerged as the most commonly used antibiotic due to its effectiveness against E. coli. The high prevalence of antibiotic resistance among other pathogens necessitates ongoing surveillance and appropriate antibiotic stewardship to combat UTIs effectively. In conclusion, this study provides valuable insights into the incidence, antibiotic resistance, and management of UTIs in Sulaymaniah city. It emphasizes the need for tailored treatment approaches considering the prevalent causative agents and their susceptibility patterns.